Pre-existing salt structures and the folding of the Zagros Mountains - Callot, Jean-Paul; Trocmé, Vincent; Letouzey, Jean; Albouy, Emily; Jahani, Salman; Sherkati, Sharam (Salt Tectonics, Sediments and Prospectivity, 2012)
Four-dimensional analogue X-ray tomography imagery is used to investigate the role played by pre-existing salt structures during compressive deformation. Initially linear salt structures evolve towards more axisymmetric diapirs. Depending on the diapir geometry and on its thickness relative to the sedimentary column thickness, the diapirs are either (1) shortened and localize sharp overturned folds for vertical pipe-like diapirs or else (2) act as preferentially oriented ramps, the diapir being incorporated in the fold for pillow-like diapirs. The ridges have a strong effect on the lateral extent and orientation of folds: they disconnect the folds formed on either side of the salt wall. Compressional relays between ridges allow for a folded connection between both sides. The Zagros Mountains in southern Iran offer a large variety of comparable structures, associated with the Hormuz salt level which acts as the regional décollement. Most of the salt structures have been active from the Early Palaeozoic until the present day. The first-order critical taper is controlled by the distribution of Hormuz décollement level and by its thickness. At a smaller scale, the fold geometry and size are locally controlled by the pre-existing salt structures, which are the main source of heterogeneity in the deformation.